Innowacyjność w karbach konwencji. O pierwszym podręczniku do nauki języka angielskiego dla Polaków = Innovation restricted by Convention. About the first Handbook of English for Poles - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a contribution to the systematic linguistic studies devoted to the first handbook of English written by a Pole (1788). The text presents the preliminary results of analyzes carried out from the pragmatic and genre studies perspective . These analyses have focused mainly on stylistic layer of the text.
Keywords: dawne podręczniki do nauki języków obcych; edukacyjność; ukształtowanie stylistyczne tekstów; Antonowicz, Julian (ok. 1750-1824); the former Polish handbooks of learning foreign languages; educational texts; the stylistic features of texts